Wybrane problemy społeczne środowisk wiejskich (ze szczególnym uwzględnieniem kwestii edukacji młodego pokolenia wsi) - Matysiak-Błaszczyk, Agata; Słupska, Kamila (Wydawnictwo Naukowe UAM, 2013)
The article deals with selected social problems of the rural environment, with particular emphasis on the situation of young people. The intention of the authors was also to show the living conditions and the diffi culties faced by people living in rural areas. The authors refer in the article to the selected reports and socio-pedagogical diagnosis of the local environment in rural areas of Poland.
Selected Social Problems of Rural Areas (With Special Emphasis on the Education of the Young Generation)
Keywords: social problem; youth; village; education